Microscopy, XRF and FTIR data from the project Medieval timber houses in Dalarna, project code RAÄ-2025-1685 - Canosa, Elyse (Swedish National Heritage Board, 2026)
Samples from medieval wooden doors in Dalarna, Sweden were sent by the County Administrative Board of Dalarna to the Heritage Laboratory at the Swedish National Heritage Board for analysis. The research question was to determine whether the doors are coated with tar or another substance. Data from the following analytical techniques is included: 1. X-ray fluorescence spectroscopy (XRF); 2. Fourier transform infrared spectroscopy (FTIR); 3. visible and UV light optical microscopy. Instrument reports are also included. Project code RAÄ-2025-1685. The analysis report compiling the data and the final report from the County Administrative Board of Dalarna can be found at: 10.5281/zenodo.18430769.
Keywords: RAÄ-2025-1685; Dalarna; Sweden; Heritage Science; Tar; Medieval buildings; Timber; x-ray fluorescence spectroscopy; Spectroscopy, Fourier Transform Infrared; Microscopy; History and Archaeology; Historia och arkeologi